Drinking Refusal Self-Efficacy Among Child and Adolescents - Sethabouppha, Hunsa; Rakthunyakarn, Priyakorn; Wongchai, Nawarat; Tamdee, Decha; Langka, Preeyakorn (Academic Psychiatry and Psychology Journal, 2019)
Objective: To explore the drinking refusal self-efficacy among children and adolescents Materials and Method: This was a descriptive study. Six hundred and sixty-six children and adolescents studying in a municipal school in the upper northern region of Thailand were selected by using multistage random sampling. Data were collected from January to February of 2019. The Drinking Refusal Self-Efficacy Questionnaires – Shortened Adolescent Version: was used. Data analysis employed descriptive statistics. Results: Samples were 311 boys and 305 girls (50.5% and 49.5%). Numbers in each educational level were 172 in elementary level (grade 4-6), 252 in junior high school (grade 1-3), and 192 senior high school (grade 4-6) (28%, 40.9%, and 31.1% respectively). Three hundred and sixty-six students reported high scores of drinking refusal self-efficacy, while 250 reported low scores (59.4 % and 40.6%). According to the educational level, senior high school (grade 4-6) students were reported to have the highest number of low scores, then junior high school (grade 1-3) students and elementary level (grade 4-6) students, respectively (41.7%, 38.1%, and 36.0%). Regarding the low scores in each dimension, the emotional relief refusal efficacy dimension was reported the highest, then the social pressure refusal efficacy dimension, and the opportunistic refusal efficacy dimension, respectively (43.2%, 40.6%, and 27.1%). Conclusion: Almost halves of the sample groups in this study presented low scores of drinking refusal self-efficacy.